Association between self-reported eye conditions in patients at rural federally qualified health centers and vision-targeted health-related quality of life: the AL-SIGHT study - Swain, Thomas A.; McGwin, Gerald; Rhodes, Lindsay A.; Girkin, Christopher A.; Owsley, Cynthia (Frontiers in Medicine, 2025)
BackgroundFederally Qualified Health Centers (FQHCs) are safety-net primary health care clinics in the US serving medically underserved areas and populations. We administered the National Eye Institute Visual Function Questionnaire – 9 (VFQ-9), a vision-targeted, health-related quality of life questionnaire, to patients in 3 FQHCs in rural Alabama at risk for glaucoma. We examined demographic factors and self-reported eye conditions associated with VFQ-9 scores.MethodsThe VFQ-9 (score range 0–100) was administered to patients at-risk for glaucoma including African Americans or Hispanics ≥40 years, white persons ≥50 years, persons with diabetes ≥18 years, ≥18 years with glaucoma or glaucoma suspect, and/or ≥ 18 years with a family history of glaucoma. Demographic variables were collected -- age, gender, race/ethnicity, employment, marital status, health insurance, education, and driving status. Patients reported the presence of eye conditions including glaucoma and many other eye conditions. Stepwise linear regression modeled which variables accounted for the greatest variance of the VFQ-9 score.ResultsComposite VFQ-9 scores averaged 82.4. The best fitting model for VFQ-9 scores included being a driver, insurance type/status, self-reported glaucoma or glaucoma suspect, blurry vision, and double vision.ConclusionPatients at-risk for glaucoma seeking care at FQHCs in rural Alabama have moderate impairment in quality of life as assessed by the VFQ-9. Factors negatively influencing scores are self-reported glaucoma or glaucoma suspect, blurry vision, double vision, not being a driver, and having no health insurance. The VFQ-9 is a good candidate as a vision-targeted quality of life outcome for eye health interventions at rural FQHCs in those with glaucoma.